More Than Just Resistance: Understanding Bacterial Defense Mechanisms as a Source of Future Antibiotics - A Literature Review - Safitri, Elza (RADINKA JOURNAL OF HEALTH SCIENCE, 2025)
The antibiotic resistance crisis is no longer just a medical issue, but has become an urgent global health threat that has the potential to cripple progress in treating infections. The aim of this study was to review More Than Just Resistance: Understanding Bacterial Defense Mechanisms as a Source of Future Antibiotics - A Literature Review. This method is a more rigorous and structured approach than a traditional literature review. Results of the study Studying bacterial defense mechanisms in depth can reveal new molecular targets that are essential for bacterial survival or virulence, but different from those of traditional antibiotics. Attacking these targets can disable bacteria or make them more susceptible to the immune system or existing antibiotics. Examples include targeting efflux pumps, biofilm-forming components, or bacterial DNA repair systems. Development of Defense Mechanism Inhibitors: Instead of killing bacteria directly, we can develop molecules that specifically inhibit their defense mechanisms.